PROGRAM REVITALISASI MELALUI PENERANGAN JALAN (PJU) DI DESA PANGLUNGAN KECAMATAN WONOSALAM KABUPATEN JOMBANG - Anggi Maiyanti, Aziza; Miftakus Surur, Agus; Syaifullah, Ainun; Nur Fadillah, Evi (Proceedings of Annual Conference on Community Engagement, 2023)
The general objective of this research is to provide solutions to the problems that the Panglungan Village is experiencing. With such public street lights, in addition to lighting the road, it is also useful to maintain public safety. The research was conducted at Dusun Panglungan Ds. Panglongan Kec. Wonosalam Kab. Jombang Province East Java. This type of research uses the PAR method.( Participatory Research). Where the data collection methods used in this research are observation, documentation and interview methods. The results of the research show that the Revitalization of Public Street Lighting program in Panglungan Village is very beneficial to the surrounding population especially when active at night.